2015
DOI: 10.1120/jacmp.v16i4.5194
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using respiration‐averaged MR images for attenuation correction of cardiac PET/MR imaging

Abstract: Cardiac imaging is a promising application for combined PET/MR imaging. However, current MR imaging protocols for whole‐body attenuation correction can produce spatial mismatch between PET and MR‐derived attenuation data owing to a disparity between the two modalities' imaging speeds. We assessed the feasibility of using a respiration‐averaged MR (AMR) method for attenuation correction of cardiac PET data in PET/MR images. First, to demonstrate the feasibility of motion imaging with MR, we used a 3T MR system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The appearance of the artifacts was reminiscent of artifacts at the diaphragm arising from mismatch of the PET emission and attenuation data because of respiratory motion, which has been previously noted on both PET/CT and PET/MR imaging (23,24). The need for matching attenuation and PET data has also been previously described for cardiac PET/MR imaging (25). In addition, we observed that the bronchi were not segmented from the surrounding structures in the attenuation maps produced by the standard MR imaging protocol ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of the artifacts was reminiscent of artifacts at the diaphragm arising from mismatch of the PET emission and attenuation data because of respiratory motion, which has been previously noted on both PET/CT and PET/MR imaging (23,24). The need for matching attenuation and PET data has also been previously described for cardiac PET/MR imaging (25). In addition, we observed that the bronchi were not segmented from the surrounding structures in the attenuation maps produced by the standard MR imaging protocol ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notice that PET/CT data would still not constitute a standard of reference. Barring sophisticated approaches not used in clinical practice (eg, attenuation correction on the basis of dynamic CT) (17)(18)(19)(20), there is no practical way to estimate patient attenuation in the presence of respiratory motion.Voxel-wise maps offer the most intuitive representation of the bias that respiratory mismatch can introduce in PET ). Notice how normalized error values larger than 610% can be found over the entire lung contour.…”
mentioning
confidence: 99%
“…Ai and Pan demonstrated the feasibility of using respiration‐averaged MRI on one patient. Using a two‐dimensional (2D) multi‐slice, multi‐phase spoiled gradient‐recalled echo sequence they acquired 12 consecutive time frames at each slice location to have good coverage over the full respiratory cycle at each slice location.…”
Section: Past and Present Attenuation Estimation Methodsmentioning
confidence: 99%